Characteristics and factors influencing Pb(II) desorption from a Chinese clay by citric acid. Issue 17 (21st November 2016) - Tang, Qiang; Chu, Jiaming; Wang, Yan; Zhou, Ting; Liu, Yang
ABSTRACT: Soil contamination by heavy metals has attracted worldwide attention, since its highly toxicity and potential threaten to the human health. Thus, in this study, the desorption behaviors of Pb(II) by citric acid from a Chinese clay were evaluated. According to the results, Pb(II) removal percentage reached around 60% within 2 h. The acidic condition, relative high concentration of citric acid and contamination levels were found to be beneficial for Pb(II) desorption. During the desorption process, the originally fixed Pb(II) was first replaced by H +, especially at low selectivity sorption sites. The released Pb(II) was then chelated by organic ligands from citric acid.